Pelatihan Bahasa Inggris Komunikatif Dalam Rangka Pengembangan Pura Dalem Ped Sebagai Objek Wisata Religi - I Ketut Subagia; Nyoman Sujaya; Anak Agung Inten Mayuni; Ni Nyoman Kertiasih (Universitas Warmadewa, 2025)
This community service empowers the community in the field of communicative English knowledge. The target is pecalangs (the security) who work for the Dalem Ped temple. The service which gives training about communicative English aims at optimizing the pecalang's ability to communicate using English. This is necessary to be done so that the pecalang at the Dalem Ped temple are able to serve and supervise visitors who come not only from Bali and outside Bali but also from abroad so that service to visitors and order in maintaining the sanctity of the temple can be handled. The methods applied include direct observation, recording problems faced by partners, preparing modules and books, giving lectures, mentoring, simulations and evaluations. To increase understanding, the service team has also donated the book